Strategies Employed by Teachers in the Instruction of Reading Comprehension - Cai Yun Pu (Majapahit Journal of English Studies, 2025)
This study aimed to identify the reading instruction strategies employed by English teachers and how these strategies were implemented in the classroom.  This study followed a descriptive qualitative methodology.  Two first-grade English teachers from the school participated in the study.  The researcher watched each English teacher have two meetings.  A checklist of strategies and in-depth interviews served as the research tools.  The goals of the study were to determine the methods employed by English teachers and the extent to which these strategies were applied in the instruction of reading comprehension.  The data analysis process had three distinct phases: data reduction, data display, and interpretation or conclusion drawing.  Teacher, one employed a variety of tactics to help her students understand what they read, according to the results.  Methods included coming up with ideas, reading out loud, and requesting detailed information.  Two instructors employed nine different approaches.  The use of dictionaries, reading aloud, rereading to check understanding, assessing understanding in specific activities, and asking questions to get specific information were all things they were pushing for.  The methods for teaching reading comprehension were divided into three stages, and both instructors used and blended them.  Reading itself was divided into three phases: pre-reading, during-reading, and post-reading.  Reading comprehension was a strong subject area for instruction at that institution because of the tactics used.  The kids' enthusiasm, the students' focus, and the teachers' comfort level during the lesson were all indicators of this.